Occipital Condyle Fracture with Accompanying Meningeal Spinal Cysts as a result of Cervical Spine Injury in 15-Year-Old Girl. (12th October 2015) - Wiktor, Łukasz; Tomaszewski, Ryszard
Abstract : The occipital condyle fracture is rare injury of the craniocervical junction. Meningeal spinal cysts are rare tumors of the spinal cord. Depending on location, these lesions may be classified as extradural and subdural, but extradural spinal cysts are more common. We present the case of a 15-year-old girl who suffered from avulsion occipital condyle fracture treated with use of "halo-vest" system. We established that clinical effect after completed treatment is very good. Control MRI evaluation was performed 12 months after removal of "halo-vest" traction, and clinically silent extradural meningeal spinal cysts were detected at the ventral side of the spinal cord in the cervical segment of the spine. Due to clinically silent course of the disease, we decided to use the conservative treatment. The patient remains under control of our department.